West African languages enrich the frequency code: Multi-functional pitch and multi-dimensional prosody in Ikaan polar questions. Issue 1 (7th June 2017) - Salffner, Sophie
Abstract : Cross-linguistically, statements tend to be pronounced with low or falling pitch and questions with high or rising pitch, a form–meaning pairing which has been attributed to the frequency code (Ohala, 1984 ). In many West African languages, however, questions are marked with a 'lax' prosody comprising falling intonation, low tones, lengthening, breathy termination, and open vowels (Rialland, 2007 ). This paper presents prosody findings from Ikaan (Niger-Congo; ISO 639-3: kcf) and proposes a re-analysis of the West African lax question prosody to integrate it with the frequency code model. The paper shows that the pragmatic functions of statement and polar question are expressed prosodically in Ikaan. Audio recordings of statements and morphosyntactically identical polar questions by six speakers were annotated segmentally, tonally, and for the presence of prosodic question markers. Speakers mark questions by using higher onset pitch, wider drops to final low tones, final breathy voice and voicelessness, final vowel lengthening, vowel insertion, and increased intensity. Breathiness may further contrast with creaky voice and glottal stops in statements. Phonation mode, and the accompanying vowel lengthening and insertion, are argued to indicate friendliness and appeals for collaboration, linking phonation mode to similar functions of higher pitch in the frequency code.